Romantic empiricism - Nassar, Dalia (Oxford University Press, 2022)
In Romantic Empiricism, Dalia Nassar distinguishes and explores an understudied philosophical tradition that emerged in Germany in the late eighteenth and early nineteenth centuries, traces its development, and argues for its continued significance. Moving from the late Kant's notion of reflecting judgment, to Herder's articulation of the idea of
9780190095437
Keywords: Westliche Philosophie: Neuzeit; Wissenschaftstheorie; Wissenschaftsphilosophie; Ästhetik; Sprachphilosophie; Erkenntnistheorie; Philosophy of science; Philosophy: aesthetics; Philosophy of language; Philosophy: epistemology & theory of knowledge